Implementation and Evaluation of an Improved Lake Scheme in Beijing Climate Center Atmosphere‐Vegetation Interaction Model. Issue 9 (28th April 2020) - Qiu, Bo; Huang, Anning; Shi, Xueli; Dai, Yongjiu; Wei, Nan; Guo, Weidong; Li, Weiping; Lazhu; Zhang, Yanwu; Fu, Zhipeng; Ling, Xiaolu
Abstract: To improve the performance of the second generation of Beijing Climate Center Atmosphere‐Vegetation Interaction Model (BCC_AVIM2.0) with a fine resolution (~45 km) over lake‐rich areas, the default lake scheme in BCC_AVIM2.0 is replaced by the Common Land Surface Model (CoLM)‐Lake scheme with much more realistic treatments of the energy exchanges in the snow‐ice‐water‐sediment system relative to the default lake scheme. Results show that the lake surface temperature (LST) biases produced by BCC_AVIM2.0 with the default lake scheme can be largely reduced by adopting the CoLM‐Lake scheme in winter due to much more realistically simulated vertical water temperature profiles over the Great Lakes region. The spatial distributions and seasonal variations of the LST simulations can also be significantly improved by the CoLM‐Lake scheme within BCC_AVIM2.0. The performances of BCC_AVIM2.0 in simulating the lake ice in winter can be largely improved by replacing the default lake scheme with the CoLM‐Lake scheme. The improvements in the LST simulated by BCC_AVIM2.0 with the CoLM‐Lake scheme further lead to reduced biases in the simulated ground surface temperature. The simulations of air temperature and precipitation in the coupled model are also improved by adopting the CoLM‐Lake scheme over the Great Lakes region, which indicates the improvements in simulating the energy and water exchange between the atmosphere and lakes. This study highlights the importance of a more realistic lake scheme in simulating the ground surface temperature and the energy exchanges between the atmosphere and lakes. Key Points: The default lake scheme in BCC_AVIM2.0 is replaced by the CoLM‐Lake scheme Lake water temperature biases produced by the default lake scheme are largely reduced by adopting the CoLM‐Lake scheme Large improvements in simulating lake ice are obtained by adopting the CoLM‐Lake scheme in BCC_AVIM2.0